2013
DOI: 10.1155/2013/473495
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of the Weld Bead Geometry in Submerged Arc Welding by Using Adaptive Neurofuzzy Inference System

Abstract: This study is aimed at obtaining a relationship between the values defining bead geometry and the welding parameters and also to select optimum welding parameters. For this reason, an experimental study has been realized. The welding parameters such as the arc current, arc voltage, and welding speed which have the most effect on bead geometry are considered, and the other parameters are held as constant. Four, three, and five different values for the arc current, the arc voltage, and welding speed are used, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The analysed documents work mainly in horizontal or flat welding and obtain static models that use algorithms of artificial intelligence. The algorithms of artificial intelligence (represented by artificial neural networks [2,6,[42][43][44][45][46], fuzzy logic [47][48][49] and their combinations) are the most used to estimate the weld bead geometry and represent 28% of the works found in the literature. Image processing and statistical techniques such as multiple regression analysis, least squares [43,50,51] or factorial design [52] are also frequently used.…”
Section: Estimation Of the Weld Bead Depthmentioning
confidence: 99%
“…The analysed documents work mainly in horizontal or flat welding and obtain static models that use algorithms of artificial intelligence. The algorithms of artificial intelligence (represented by artificial neural networks [2,6,[42][43][44][45][46], fuzzy logic [47][48][49] and their combinations) are the most used to estimate the weld bead geometry and represent 28% of the works found in the literature. Image processing and statistical techniques such as multiple regression analysis, least squares [43,50,51] or factorial design [52] are also frequently used.…”
Section: Estimation Of the Weld Bead Depthmentioning
confidence: 99%
“…However, the welding joints are often the weakest links in assemblies [9]. The quality of the weld depends on the bead geometry [10], metallurgical and mechanical characteristics [11], chemical composition [12], and input parameters such as voltage, current, electrode type, flux and gas type, welding position, travel speed, and others [4] making the task of finding the best parameters quite challenging [13]. If the welding parameters are not correctly chosen, they can lead to welded joints with high levels of residual stresses [14,15], geometric distortions [16], and discontinuities [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The research revealed that the optimisation of hard facing welding conditions can both result in improved properties and reduce the cost of manufacture. Akkas et al (2013) developed the models correlating the welding process parameters with the bead geometry of the welds. To correlate the above, ANN and neuro-fuzzy system approachs were used.…”
Section: Introductionmentioning
confidence: 99%